2021
DOI: 10.1002/1878-0261.13084
|View full text |Cite
|
Sign up to set email alerts
|

A novel anti‐c‐Kit antibody–drug conjugate to treat wild‐type and activating‐mutant c‐Kit‐positive tumors

Abstract: c-Kit overexpression and activating mutations, which are reported in various cancers, including gastrointestinal stromal tumor (GIST), small-cell lung cancer (SCLC), acute myeloid leukemia, acral melanoma, and systemic mastocytosis (SM), confer resistance to tyrosine kinase inhibitors (TKIs). To overcome TKI resistance, an anti-c-Kit antibody-drug conjugate was developed in this study to treat wild-type and mutant c-Kitpositive cancers. NN2101, a fully human IgG1, was conjugated to DM1, a microtubule inhibitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 76 publications
(111 reference statements)
1
21
1
Order By: Relevance
“…Interestingly, 4C9 antibody binding was saturated at 50 ng/mL in c-Kit-positive SCLC cell lines. In addition, the expression of c-Kit was higher in NCI-H889 cells compared with that in NCI-H526 and NCI-H1048 cells, which is consistent with a previous report [34]. However, 4C9 did not show cross-reactivity with NCI-H446 and NCI-H2170 cells, which are c-Kit-negative SCLC cell lines.…”
Section: C9 Antibody Specifically Binds To C-kitsupporting
confidence: 91%
See 2 more Smart Citations
“…Interestingly, 4C9 antibody binding was saturated at 50 ng/mL in c-Kit-positive SCLC cell lines. In addition, the expression of c-Kit was higher in NCI-H889 cells compared with that in NCI-H526 and NCI-H1048 cells, which is consistent with a previous report [34]. However, 4C9 did not show cross-reactivity with NCI-H446 and NCI-H2170 cells, which are c-Kit-negative SCLC cell lines.…”
Section: C9 Antibody Specifically Binds To C-kitsupporting
confidence: 91%
“…4C9 antibody (2 ng/mL) was then added to each well at RT for 1 h. The plate was washed with 1 × PBS containing 0.1% Tween-20 four times and incubated with HRP-conjugated anti-human IgG secondary antibody (1:2000; Santa Cruz Biotechnology, Santa Cruz, CA, USA) for 1 h. Then, 3, 3 , 5, 5 -tetramethylbenzidine solution (Thermo Fisher Scientific, Waltham, MA, USA) was added for 5 min. The signal was measured at 450 nm using a SPECTROstar Nano Microplate Reader (BMG LABTECH, Ortenberg, GermanyELISA was also used to compare the binding affinities of 4C9 and 4C9-DM1 as previously described [34].…”
Section: Elisamentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, we demonstrated that 2G4 and 4C9 antibodies bind to c-Kit with high binding a nity (K D of 2G4 = 2.83 × 10 − 12 M and K D of 4C9 = 5.58 × 10 − 9 M). Moreover, 2G4 antibody, as an antagonist of c-Kit, inhibited SCF/c-Kit signaling in various cancer cell lines [34,35]. In this study, the human mast cell line LAD2, which highly expresses FcεRI and c-Kit (Supplementary Fig.…”
Section: G4 Antibody Inhibits Scf/c-kit Signalingmentioning
confidence: 67%
“…To overcome the limitations of anti-IgE antibodies, we aimed to develop therapeutic antibody that can inhibit both the proliferation and degranulation of mast cells. Previous studies have demonstrated that 2G4 antibody, a fully human antibody, could inhibit the activation of SCF/c-Kit signaling in various cancer cell lines [34,35]. In addition, another anti-c-Kit antibody 4C9 signi cantly reduced the expression of c-Kit [36].…”
Section: Introductionmentioning
confidence: 99%